Defining Core Competencies for Epidemiologists in Academic Settings to Tackle Tomorrow's Health Research Challenges: A Structured, Multinational Effort. Issue 3 (27th October 2020) - Abraham, Alison; Gille, Doreen; Puhan, Milo A; ter Riet, Gerben; von Wyl, Viktor; ,
Abstract: Only a few efforts have been made to define core competencies for epidemiologists working in academic settings. Here we describe a multinational effort to define competencies for epidemiologists, who are increasingly facing emerging and potentially disruptive technological and societal health trends in academic research. During a 1.5-year period (2017–2019), we followed an iterative process that aimed to be inclusive and multinational to reflect the various perspectives of a diverse group of epidemiologists. Competencies were developed by a consortium in a consensus-oriented process that spanned 3 main activities: 2 in-person interactive meetings held in Amsterdam, the Netherlands, and Zurich, Switzerland, and an online survey. In total, 93 meeting participants from 16 countries and 173 respondents from 19 countries contributed to the development of 31 competencies. These 31 competencies included 14 on "developing a scientific question" and "study planning, " 12 on "study conduct and analysis, " 3 on "overarching competencies, " and 2 on "communication and translation." The process described here provides a consensus-based framework for defining and adapting the field. It should initiate a continuous process of thinking about competencies and the implications for teaching epidemiology to ensure that epidemiologists working in academic settings are well prepared for today's and tomorrow's health research.